Men's Understanding of and Experiences During the Postcircumcision Abstinence Period: Results From a Field Study of ShangRing Circumcision During Routine Clinical Services in Kenya and Zambia. (1st June 2016) - Barone, Mark A.; Li, Philip S.; Zulu, Robert; Awori, Quentin D.; Agot, Kawango; Combes, Stephanie; Simba, Raymond O.; Lee, Richard K.; Hart, Catherine; Lai, Jaim Jou; Zyambo, Zude; Goldstein, Marc; et al.
Abstract : Background: Men's understanding of counseling messages after voluntary medical male circumcision (VMMC) plays an important role in whether they follow them. Data on triggers for early resumption of sex may be useful as scale-up of VMMC for HIV prevention continues in sub-Saharan Africa. Methods: Data on understanding of post-VMMC abstinence recommendations, resumption of sex, condom use, and triggers for resuming sex were collected from participants during a follow-up interview 35–42 days after ShangRing circumcision in Kenya and Zambia. Results: Of 1149 men who had ShangRing circumcision, 1096 (95.4%) completed follow-up. Nearly all (99.2%) reported being counseled to abstain from sex post-VMMC; among those, most (92.2%) recalled the recommended abstinence period was 6 weeks. Most men (94.1%) reported that the counselor gave reasons for post-VMMC abstinence and recalled appropriate reasons. Few (13.4%) men reported resuming sex at 35–42 days' follow-up. Among those, 54.8% reported never using a condom post-VMMC. Younger participants (odds ratio 0.3, 95% confidence interval: 0.2 to 0.5, P < 0.0001) and those reporting at least some condom use at baseline (odds ratio 0.5, 95% confidence interval: 0.3 to 0.7, P = 0.0003) were less likely to report resuming sex. Among men who reported some condom use, most (71.5%) said condoms were much easier or easier to use after circumcision. Men reported various reasons for early resumption of sex, primarily strong sexual desire (76.4%). Conclusions: Most men reported awareness of and adherence to the counseling recommendations for post-VMMC abstinence. A minority reported early resumption of sex, and, among those, condom use was low. Results could be used to improve post-VMMC counseling.